The impact of genetic polymorphisms on genotoxicity in workers occupationally exposed to pesticides: a systematic review - Guedes Pinto, Thiago; da Silva, Glenda Nicioli; Renno, Ana Claudia Muniz; Salvadori, Daisy Maria Favero [UNESP]; Ribeiro, Daniel Araki (Taylor & Francis, 2024)
In a world with a rising use of pesticides, these chemicals, although designed to effectively control pests, pose potential threats to the environment and non-target organisms, including humans. Thus, this systematic review aims to investigate a possible association between genetic polymorphisms and susceptibility and genotoxicity in individuals occupationally exposed to pesticides. This review was conducted following the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. A total of 14 carefully selected studies were thoroughly analyzed by two reviewers, who assigned scores based on previously set evaluation criteria. This study classified over half of the chosen studies as having moderate or strong quality, observing a correlation between certain genetic polymorphisms involved in xenobiotic metabolism and genotoxicity in workers exposed to pesticides. Results suggest that the genes associated with xenobiotic metabolism play a substantial role in determining individuals’ susceptibility to genomic damage due to pesticide exposure, affecting both their peripheral blood and oral mucosa. This implies that individuals with specific genotypes may experience increased or decreased levels of DNA damage when exposed to these chemicals.
Keywords: DNA damage; genetic polymorphism; Genotoxicity; pesticides